Pengaruh Eksploitasi Sumber Daya Alam Perairan Terhadap Kemiskinan Pada Masyarakat Nelayan - Feryl Ilyasa; Zid, Muhammad; Miarsyah, Mieke (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2020)
The aim of this article is to find out how the influence of exploitation of aquatic natural resources on the poverty of fishing communities. The method in this article used a descriptive research design for using a literature study approach. Based on the type of research and the type of data source used, the data collection technique in this study is used the secondary data. The results in this study can be seen in two aspects, are: (1) the ease of foreign investments that can be exploit for the natural resources of fisheries in Indonesia; (2) the influence of exploitation of the natural resources of the waters carried out on poverty in the fisihing community. Exploitation of aquatic natural resources in Indonesia is due to the ease with which foreign parties can be invest in Indonesia in the field of fisheries, and then this ease of investment from foreign parties results in the intervention of foreign parties who can to control the natural waters resources in Indonesia, both in the form a legal entitiy or in the form of an individual, it can be also for drain the natural waters resources, especially fisheries in Indonesia, and which can to be affect the walfare of fishing communities.